If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7a + 6b + 2a + -3b + 2a + 3b + -5a + -4b = 0 Reorder the terms: 7a + 2a + 2a + -5a + 6b + -3b + 3b + -4b = 0 Combine like terms: 7a + 2a = 9a 9a + 2a + -5a + 6b + -3b + 3b + -4b = 0 Combine like terms: 9a + 2a = 11a 11a + -5a + 6b + -3b + 3b + -4b = 0 Combine like terms: 11a + -5a = 6a 6a + 6b + -3b + 3b + -4b = 0 Combine like terms: 6b + -3b = 3b 6a + 3b + 3b + -4b = 0 Combine like terms: 3b + 3b = 6b 6a + 6b + -4b = 0 Combine like terms: 6b + -4b = 2b 6a + 2b = 0 Solving 6a + 2b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2b' to each side of the equation. 6a + 2b + -2b = 0 + -2b Combine like terms: 2b + -2b = 0 6a + 0 = 0 + -2b 6a = 0 + -2b Remove the zero: 6a = -2b Divide each side by '6'. a = -0.3333333333b Simplifying a = -0.3333333333b
| 2(x)-9=180-x | | 5/18-(-1/3) | | 23-3X=14+2X | | -21b^2+39b+6= | | 2(x)-9=180-y | | -1/7+(-3/7) | | K-12=6 | | -0.5x-3=-0.25x-5 | | 2x^3y+11x^2y+15xy= | | 14+3X=23-2X | | 5x*5=60x*4 | | -x+4=-21 | | 0.9x-1.9=1.5x+2.1 | | 0.5x+3=0.25x+5 | | 0.75x-5=4 | | 5x*5=60 | | x=90-x+22 | | -5+5(x-4)=12x+4-7x | | 28=3m-1d | | 6(1+9c)=-17 | | 2000x/5=50 | | 100x/2=50 | | 32u^2+16uv+2v^2= | | (2*1000*4/2,5)= | | 2x*5=100 | | 0.75x-5=-4 | | 3+4x=7x+27 | | x*x-3=0 | | 0.66666666666667x-0.25=-0.2x+0.11111111111111 | | 3+4x=6x+27 | | -3v+8-5=29 | | 5x+2=2(2x-3)+8 |